ISLAMIZATION OF ECONOMY IN INDONESIA:From Politics to Law - Waldi Nopriansyah (Jurnal Hikmatuna, 2019)
Abstract Looking at the historical record, the process of Islamization of economy in Indonesia has faced enormous challenges. The challenges, for instance, come from politics, in which the Islamization of economy was initially rejected before it finally gained acceptance in 1991. The challenges also emerge from law where it was initially not supported by the existing legal rules. The law dealing with Islamic economy in the country first existed in 1992, concerning the Islamic banking operations. This article examines the Islamization of economy in Indonesia in terms of politics and law. Using a qualitative method with historical perspective on politics and law, the writer first describes the journey of the Islamization of economy from a number of literatures, and then analyzes it from political and legal perspective. He argues that politics in Indonesia has an important influence on the recognition and acceptance of the Islamization of economy. Likewise, law in Indonesia has an important role regarding legal certainty of the Islamization of economy in the country.